The effective amount of rice / paddy husk that generate smoke to control the storage beetle: a research / Muhammad Adil Zulkipli - Zulkipli, Muhammad Adil (Faculty of Plantation and Agrotechnology, 2018)
In Malaysia, the amount of insecticide to control the insect pest can give the effect to human health and environment. The introduction of chemical made the traditional method become more forgotten. In this modern agrotechnology some examples of traditional storage methods are given to bring them back into memory. Not every method will be effective in certain situation try some of them out and experiment it for your own self. The main objective of this research is to determine the effective amount of paddy or rice husk that generate smoke to control the storage beetle in rice. The location of this study was carried out at Tanjung Karang Selangor because the location is basically one of the main rice productions for example BERNAS mill. Two different insects were chosen first is Rice weevil (Sitophilus oryzae) and second is Red-rust flour beetle (Tribolium castaneum) because this beetle is the main storage beetle that attacks the storage product. The different weight of paddy or rice husk been experimented and the best weight to control the beetle is 5 kilogram and the best length period of time is under 15 minutes for the insect to reach it mortality level. The smoke that been generated from the rice husk can save the cost because the rice husk is a byproduct from the rice mill processing and can reduce the use of insecticide.